Kepemimpinan Profetik Masa Bani Umayyah - Toha Ma'sum (Intizam, Jurnal Manajemen Pendidikan Islam, 2020)
Prophet Muhammad SAW is the messenger of God who became the leader of the prophets and messengers sent by God. He is the prophet and the last messenger sent by Allah SWT. As a prophet and apostle, he is also a leader in various fields of life, all movements, behaviors, and attitudes are ideal examples for humanity. Other qualities possessed by the previous prophets, also became part of his character, including in terms of his leadership. Prophetic values ​​which in contemporary terms often call it by the term of prophetic. Prophetic leadership is defined as the leader’s ability to control himself and influence others to achieve common goals by imitating the lives of the prophets. The Prophet's leadership has four aspects, namely; sidiq (honest and following the truth of conscience), amanah (responsible and reliable), tabligh (communicating empathically and effectively), and fatonah (intelligent because of taqwa). Internalization of the concept, if it refers to history during the Umayyad era, the famous leadership of the prophet has four aspects, namely sidiq (honest and following the truth of conscience), amanah (responsible and reliable), tabligh (communicating empathically and effectively), and fatonah (intelligent because of taqwa) is Umar Bin Abdul Aziz. In general, leadership during the Umayyad era had applied prophetic values ​​in their respective leadership, but it was not maximized and comprehensive from the prophetic dimensions. This happened to almost all the leaders of the Umayyads, except Umar Bin Abdul Aziz, he was the only leader of that era who, in the view of historians, carried out his leadership to advocate Rosulullah and Khulafaurrosyidin, and was even given the title of the 5th Amirul of the believer after Khulafaurrosyidin. Internalization of prophetic values ​​is very much felt in his leadership, in various fields, as well as in various sides, both in himself, his family, government and people